The The Effect of Digital Leadership Style, Motivation, and Work Ability on Employee Performance After the Covid-19 Pandemic - Riski, Aulia; Rino, Rino (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study was to determine the effect of the principal's digital leadership style on performance, the Effect of personnel motivation on performance, and the Effect of personnel workability on performance as the Effect of the madrasa principal's charismatic leadership style, inspiration, and the ability of personnel to work simultaneously on the version of SMAN 1 Padang City employees after the Covid-19 pandemic. The method used is descriptive research with a quantitative approach. The data collection technique used a closed questionnaire in the form of a Google form, which was distributed to 26 employees of SMAN 1 Padang City. Based on the results of data analysis using the partial t-test and f-test simultaneously (multiple linear regression), it is known that after the COVID-19 pandemic at SMAN 1 Padang City, the school principal's charismatic leadership style positively affected employee performance with a score of 0,23. Personnel motivation does not affect employee performance with a score of 0,39; Employee workability positively affects employee performance with a score of 0,001; and the leadership style of digital school principals, motivation, and workability of employees jointly affect employee performance by 79.7%. This research has substantial implications in the post-pandemic educational context. Such substances may include the need to implement an adaptive digital leadership style, increased employee motivation, and development of employability as critical factors in improving the performance of educated employees. The information obtained from this study can help school principals and education management to more effectively manage human resources in the changing environment post-pandemic, create motivating working conditions, and improve the quality of education at SMA 1 Padang.